Exploring Financial Risks and Risk Mitigation Strategies in Digital Currencies - Wu, Ziyu (International Journal of Global Economics and Management, 2024)
This paper comprehensively analyzes the financial risks faced by digital currency, using digital renminbi as a case study. The risks include operational risks, privacy risks, legal and regulatory risks, currency sovereignty risks, and the impact on traditional financial systems. Corresponding risk mitigation strategies are proposed. By strengthening system architecture, employing advanced encryption technologies, enhancing legal and regulatory frameworks, maintaining policy stability, and promoting financial integration, these measures effectively mitigate financial risks associated with digital currency, fostering its sustainable development and innovation.